2015
DOI: 10.3109/13697137.2015.1116504
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of hormone therapy on serotonin, vascular function and mood in the KEEPS

Abstract: Background Serotonin (5-hydroxytryptamine, 5-HT) is modulated by sex steroid hormones and affects vascular function and mood. In the Kronos Early Estrogen Prevention Cognitive and Affective Ancillary Study (KEEPS-Cog), women randomized to oral conjugated equine estrogens (oCEE) showed greater benefit on affective mood states than women randomized to transdermal 17β-estradiol (tE2) or placebo (PL). This study examined the effect of these treatments on the platelet content of 5-HT as a surrogate measure of 5-HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…This is an important issue to consider, as studies have reported a greater frequency of sleep problems associated with age at discontinuation, type and duration of MHT [26,27]. Differences in various physiological parameters between o-CEE and t-E2 have been observed in women participating in KEEPS including differences in effects on lipids, glucose metabolism [28], contents of vasoactive agents in circulating platelets [15], mood [29] and brain volumes [30]. Therefore, our results add to the accumulating evidence that various types of MHT are not equal and precision is required in discussing their efficacy relative to target outcome, mode of delivery, composition and dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important issue to consider, as studies have reported a greater frequency of sleep problems associated with age at discontinuation, type and duration of MHT [26,27]. Differences in various physiological parameters between o-CEE and t-E2 have been observed in women participating in KEEPS including differences in effects on lipids, glucose metabolism [28], contents of vasoactive agents in circulating platelets [15], mood [29] and brain volumes [30]. Therefore, our results add to the accumulating evidence that various types of MHT are not equal and precision is required in discussing their efficacy relative to target outcome, mode of delivery, composition and dose.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated a subgroup of white participants (n = 74) from the Kronos Early Estrogen Prevention Study (KEEPS; NCT00154180) Cognitive and Affective Ancillary study (KEEPS-Cog) at Mayo Clinic, Rochester MN [15]. KEEPS was a randomized, double-blind, placebo-controlled trial studying the effects of MHT, started within 3 years of menopause, on progression of cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%
“…На сегодняшний день последние клинические исследования (ELITE 2016 и KEEPS 2016) подтверждают пользу раннего применения эстроген-гестагенной менопаузальной терапии с целью замедления темпов развития атеросклероза и первичной профилактики сердечно-сосудистой патологии у женщин в ранней менопаузе. При этом исследователи выдвигают временную теорию применения МГТ (раннее начало применения МГТ от возникновения менопаузы обеспечивает наилучшее протекторное действие гормонов на сосудистую стенку) как залог успешной профилактики ССЗ [17,18].…”
Section: влияние современных гормональных препаратов на систему гемосunclassified
“…vitamin D) are contradictory (12). Several studies have reported that insufficient levels of serotonin, as a neurotransmitter involved in mood and behavior, may result in depression (13)(14)(15). However, most of these reports are based on serum serotonin measurements in depressive patients (16)(17)(18), while platelet serotonin measurement is a further accurate alternative of brain serotonin (15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that insufficient levels of serotonin, as a neurotransmitter involved in mood and behavior, may result in depression (13)(14)(15). However, most of these reports are based on serum serotonin measurements in depressive patients (16)(17)(18), while platelet serotonin measurement is a further accurate alternative of brain serotonin (15,19). It is broadly accepted that dysfunction of oxytocin, another neurotransmitter, includes important roles in mood, behavior, brain development and sociality (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%